Influence of Private Sector Financing on Health Service Delivery in Level 4 Public Health Facilities in Nairobi County, Kenya - Maurice Mutua Maingi (Journal of Medicine, Nursing and Public health, 2026)
Private sector financing has increasingly become an important strategy for strengthening public healthcare systems, particularly in low- and middle-income countries where inadequate public funding constrains healthcare delivery. In Kenya, Level 4 public health facilities continue to face challenges, including insufficient financial resources, inadequate infrastructure, shortages of medical supplies, and rising demand for quality healthcare services. This study examined the role of private sector financing in improving health service delivery at Level 4 public health facilities in Nairobi County. Specifically, the study assessed the influence of private-sector financing on operational efficiency and healthcare quality, examined institutional factors affecting its integration into public healthcare, and evaluated the sustainability of private-sector financing in enhancing health service provision. The study employed a mixed-methods research design involving healthcare administrators, departmental heads, and members of sub-county health management teams in selected Level 4 public hospitals in Nairobi County. Quantitative data were analysed using descriptive and inferential statistical techniques, while qualitative data were analysed thematically to complement the quantitative findings. The findings indicate that private-sector financing significantly improves operational efficiency through enhanced infrastructure, greater availability of medical equipment, improved supply chain management, digital health innovations, and capacity building for healthcare workers. The study further established that effective institutional governance, supportive policy frameworks, stakeholder collaboration, and accountability mechanisms are essential for successful integration of private financing into public healthcare. Sustainable public-private partnerships were also found to contribute to improved healthcare quality and long-term financial resilience of public health facilities. The study concludes that strategically managed private sector financing can substantially strengthen health service delivery in Level 4 public hospitals. It recommends strengthening regulatory frameworks, promoting transparent public-private partnerships, enhancing governance structures, and developing sustainable financing models to support Universal Health Coverage and improve healthcare outcomes in Kenya.